Structural safety uncertainties in codes of practice for reinforced concrete - Neocleous, Kyriacos; Pilakoutas, Kypros; Waldron, Peter (My University, 2004)
The limit-state design approach, currently used in codified design of concrete structures reinforced with steel reinforcement, is based on semi-probabilistic procedures. Although modern concrete codes of practice are more sophisticated than older codes based on the permissible stress approach, they still have fundamental uncertainties with regards to structural safety. The work reported in this paper investigates these uncertainties for the BS 8110 and Eurocode-2 codes of practice by performing a structural reliability assessment using the Monte-Carlo Simulation method in conjunction with the Latin Hypercube and Conditional Expectation variance reduction techniques. The assessment considers both the flexural and shear failure modes. In the case of BS 8110, it is shown that it may be more appropriate to increase the characteristic value of the tensile strength of steel reinforcement rather than to use the reduced partial safety factor of 1.05. © Kyriacos Neocleous, Kyprous Pilakoutas, Peter Waldron.
Keywords: BS 8110; Design; Eurocode2; Reinforced concrete; Reliability; Safety; Structures